Coherent Diffraction Imaging with Tabletop XUV Sources - Zurch, M.; Guggenmos, A.; Jung, R.; Rothhardt, Jan; Spath, C.; Tuemmler, J.; Demmler, S.; Haedrich, S.; Limpert, Jens; Tuennermann, A.; Kleineberg, U.; Stiel, H.; et al. (Springer Proceedings in Physics, 2018)
Coherent diffraction imaging (CDI) at wavelengths in the extreme ultraviolet range has become an important tool for nanoscale investigations. Employing laser-driven high harmonic sources allows for lab-scale applications such as cancer cell classification and phase-resolved surface studies in reflection geometry. The excellent beam properties support a spatial resolution below the wavelength, i.e., close to the Abbe limit. Unfortunately, the usually low photon flux of HHG sources limits their applicability. Recent advances in ultrafast fiber laser development cumulated in sources delivering average powers approaching the milliwatt level in the extreme ultraviolet. In comparison, a tabletop soft X-ray laser driven by moderate pump energies was recently employed for CDI featuring excellent temporal coherence and extraordinary high flux allowing for single-shot imaging.
CRIS-Team Scopus Importer:2023-04-20